Human Intestinal Enteroids Model MHC-II in the Gut Epithelium - Wosen, Jonathan E.; Ilstad-Minnihan, Alexandra; Co, Julia Y.; Jiang, Wei; Mukhopadhyay, Dhriti; Fernandez-Becker, Nielsen Q.; Kuo, Calvin J.; Amieva, Manuel R.; Mellins, Elizabeth D. (Frontiers in Immunology, 2019)
The role of intestinal epithelial cells (IECs) in mucosal tolerance and immunity remains poorly understood. We present a method for inducing MHC class II (MHC-II) in human enteroids, “mini-guts” derived from small intestinal crypt stem cells, and show that the intracellular MHC-II peptide-pathway is intact and functional in IECs. Our approach enables human enteroids to be used for novel in vitro studies into IEC MHC-II regulation and function during health and disease.